Expression and Prognostic Characteristics of m6 A RNA Methylation Regulators in Breast Cancer - Zhang, Bo; Gu, Yanlin; Jiang, Guoqin (Frontiers in Genetics, 2020)
Purpose: N6-methyladenosine(m6A) is the most prevalent modification in mRNA methylation which has a wide effect on biological functions. This study aims to figure out the efficacy of m6A RNA methylation regulator-based biomarkers with prognostic significance in breast cancer. Patients and methods: The 23 RNA methylation regulators were firstly analyzed through ONCOMINE, then relative RNA-seq transcriptome and clinical data of 1096 breast cancer samples and 112 normal tissue samples were acquired from The Cancer Gene Atlas (TCGA) database. The expressive distinction was also showed by Gen Expression Omnibus (GEO) database. The gene expression data of m6A RNA regulators in human tissues were acquired from the Genotype-Tissue Expression (GTEx) database. The R v3.5.1 and other online tools such as STRING, bc-GeneExminer v4.5, Kaplan-Meier Plotter were applied for bioinformatics analysis. Results: Results from ONCOMINE, TCGA and GEO databases showed distinctive expression and clinical correlations of m6A RNA methylation regulators in breast cancer patients. The high expression of YTHDF3, ZC3H13, LRPPRC and METTL16 indicated poor survival rate in patients with breast cancer, while high expression of RBM15B points to better survival rate. Both univariate and multivariate Cox regression analyses revealed that age and risk score were related to overall survival (OS). Univariate analyses also delineated that stage, tumor (T) status, lymph node (N) status, and metastasis (M) status were associated with OS. From another perspective, Kaplan-Meier Plotter platform showed that the relatively high expression of YTHDF3 and LRPPRC and the relatively low expresssion of RBM15B, ZC3H13 and METTL16 in breast cancer patients had worse Relapse-Free Survival (RFS). Breast Cancer Gene-Expression Miner v4.5 showed that LRPPRC level was positively associated with ER and PR expression, while METTL16, RBM15B, ZC3H13 level was negatively linked with ER and PR expression. In HER-2 (+) breast cancer patients, the expression of LRPPRC, METTL16, RBM15B and ZC3H13 were all lower than the HER-2 (-) group. Conclusions: The significant difference in expression levels and prognostic value of m6A RNA methylation regulators were analyzed and validated in this study. This signature revealed the potential therapeutic value of m6A RNA methylation regulators in breast cancer.